Cookies Crafter - Besan Husam Jadallah; Lana Jaara (My University, 2025)
The cookie-making machine is an innovative and fully automated system designed to revolutionize the cookie preparation process. It combines mechanical, electronic, and programming technologies to deliver an efficient and user-friendly solution tailored to diverse needs. The system automates every step, starting with dispensing and mixing dough to achieve a homogeneous consistency. The dough is then cut into individual pieces and placed on a rotating tray, which pauses to allow the addition of chocolate based on user preferences. The tray continues to the baking section, where cookies are baked at an optimal temperature monitored by advanced sensors. To enhance functionality, the machine features an ultrasonic sensor that monitors ingredient levels and provides real-time alerts on an LCD screen for timely refills. Additionally, it features a mobile application via an ESP module, enabling remote operation, a keypad for inputting the desired number of cookies and chocolate preferences, and an RFID-based payment system for convenience. This project seamlessly integrates mechanical, electronic, and programming technologies to deliver a practical, efficient, and user-friendly solution, addressing the challenges of traditional cookie- making while paving the way for future advancements in automated food preparation. This project exemplifies how automation can redefine traditional processes, setting a benchmark for future innovations in food technology